A model for understanding SMEs internationalization in emerging economies - Zizah Che Senik; Rosmah Mat Isa; Ridzuan Md Sham; Abu H Ayob (Penerbit Universiti Kebangsaan Malaysia, 2014)
Understanding the internationalization process of small to medium-sized enterprises (SMEs) is imperative for emerging economies to compete globally. Empirical findings of SMEs from emerging countries are still lacking. Thus, this study intends to fill this gap by providing a comprehensive model for the process of SMEs internationalization in Malaysia. Five major internationalization perspectives namely process and stage models, network, born-global and international new ventures, resource-based view, and international entrepreneurship were integrated in formulating a framework for this study. In-depth interviews were carried out with thirty-two Malaysian experts including academics, policy makers, government agencies, chamber of commerce, and research institute. Interviews were transcribed and analyzed manually using thematic coding and frequency counts analysis. Six important factors with distinguished categories and items pertaining to SME internationalization process were identified: 1) triggering factors; 2) internal factors; 3) external factors; 4) networking; 5) barriers and challenges, and 6) operations for internationalization. The main contribution of this study is a generic model of SME internationalization that can provide apertures on researching into SME internationalization in emerging economies.